COMPARISON OF RADON LEVEL CONCENTRATION IN SOILS WITH THE NATURAL RADIONUCLIDES CONTENT IN SOME REGIONS OF IONAIN COASTAL AREA, IN ALBANIA - Safet Dogjani; Hamza Reci (European Scientific Journal, ESJ, 2014)
In this study we present the results taken in south-eastern part of the country, in Ionian coastal area. This study is realized into regions, in the some places in Ksamil town and Uji i Ftohte-Qeparo areas. The main sources of radon gas indoors are entirely related to the geological environment. The measurements of Radon can be realized in several ways such as: radon and permeability in soil; measurements of natural radionuclides (40K, 238U, 232Th) on the ground and soil; radon concentration level in water; measurements radon indoor in dwellings; radon level and soil permeability. Measurements (soil and permeability) have been realized using the Luka-s method. Tests have been carried out indoor at short and long measurement, using active defector with time interval 24h-72h and passive radon detectors in 3months time interval, respectively. The level of in soil Radon concentration has values from 10kBq/m3 up to160kBq/m3. From the interpretation of radon level according to Czech Classification, together with permeability of the soils results that in the two studies areas, Ksamil and „Uji i Ftohte- Qeparo“, the radon risk areas are present in 50% up to 60% of the studied area.